2002
DOI: 10.1038/emm.2002.37
|View full text |Cite
|
Sign up to set email alerts
|

Optimal salt concentration of vehicle for plasmid DNA enhances gene transfer mediated by electroporation

Abstract: In vivo electroporation has emerged as a leading technology for developing nonviral gene therapies, and the various technical parameters governing electroporation efficiency have been optimized by both theoretical and experimental analysis. However, most electroporation parameters focused on the electric conditions and the preferred vehicle for plasmid DNA injections has been normal saline. We hypothesized that salts in vehicle for plasmid DNA must affect the efficiency of DNA transfer because cations would al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 44 publications
1
35
1
Order By: Relevance
“…Usually electroporation was used for DNA vaccination at a voltage ranging from 100 V/cm to 400-1,200 V/cm [17][18][19][20] . Though the electroporation charge was applied only transiently, current studies have shown that voltages 1 100 V are an unpleasant experience for animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually electroporation was used for DNA vaccination at a voltage ranging from 100 V/cm to 400-1,200 V/cm [17][18][19][20] . Though the electroporation charge was applied only transiently, current studies have shown that voltages 1 100 V are an unpleasant experience for animals.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the electroporation voltage used, the greater the pain inflicted. A review of the literature showed that the voltages for electroporation generally range from 100 to 1,200 V/CM [17][18][19][20] . We studied the effect of DNA vaccination when electroporation was performed at lower voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, animals were anaesthetised with isoflurane and the lower hindlimbs were shaved and sterilised (iodine and 70% ethanol [vol./vol.]). To increase transfection efficiency [18][19][20] [20]). …”
Section: Descriptive Characteristics Of Lean and Obese Zucker Ratsmentioning
confidence: 99%
“…The tibialis anterior (TA) muscle was surgically exposed. Ten micrograms of plasmid DNA in 10 µl of sterile MilliQ water (Millipore Corp., Billerica, Massachusetts, USA), was layered over the muscle surface (Lee et al 2002). Silver electrodes were placed on either side of the muscle, touching the surface of the DNA solution but not the muscle.…”
Section: Electroporation Of Muscle Fibresmentioning
confidence: 99%